Development of functional micelles from biodegradable amphiphilic block copolymers for drug delivery and tumour therapy - Gulfam, Muhammad (2017)
Drug delivery systems in the size range of ~ 10-250 nm are enabling tools for site-specific targeting and controlled release applications. To take advantage of these capabilities, various nanocarriers e.g., micelles, dendrimers, liposomes, nanoparticles, nanocapsules, nanotubes, and nanogels, have been designed for drug delivery. Specifically, micelle-based drug carrier systems have emerged as promising tools for site-specific delivery and controlled release applications. Despite several advantages over conventional drugs, some limitations of micelle-based drug delivery have also been reported. These drawbacks include low stability in vivo, poor penetration, modest accumulation in tumour tissues, and inadequate control over drug release. To overcome these limitations, stimuli-responsive or smart polymeric nanocarriers have been developed for drug delivery and tumour therapy, previously. The most well-known internal stimuli in cancerous regions include higher acidity associated with dysregulated metabolism in tumour tissues, elevated levels of glutathione in the cytosol and nucleus of cancer cells, and altered degradative enzymes in the lysosomes, and reactive oxygen species in the mitochondria. These intrinsic microenvironments can be exploited as internal stimuli to attain active drug release in the tumour tissues or cancer cells. In particular, the reducing potential inside the cancer cells is considerably higher than found in the extracellular environment and bloodstream. Such varying redox potential can be exploited for tumour-specific drug delivery and controlled release applications. Various types of redox-responsive micelles have been developed, previously. Generally, redox-responsive micelles have disulfide linkages that undergo rapid cleavage in the presence of reducing agents in the intracellular components, however, are stable at oxidising extracellular environment. The redox-responsive disulfide bridges can be incorporated into nanocarriers by placing multiple disulfide bonds in the hydrophobic backbone or by conjugating therapeutic agents to the side chain of the polymer via a disulfide linker. Another strategy to construct redox-responsive linkages is to crosslink the polymeric nanocarriers with a disulfide crosslinker. Studies have shown that polymeric micelles can dissociate, especially upon administration when they are diluted below their critical micelle concentration. The stability of polymeric micelles can be enhanced by chemical crosslinking. Various types of crosslinked micelles can be prepared subjected to the localisation of the crosslinking, e.g. shell crosslinked micelles, and core crosslinked micelles. Introducing redox-responsive bridges through disulfide crosslinkers may not only provide stability to nano-carriers against dilutions during circulation, but also render them responsive to reducing conditions. Specifically, redox-responsive core-crosslinked micelles have demonstrated good stability and better ‘stealth’ properties, nevertheless, the hydrophobic core of most of the existing core-crosslinked micelles have been based on non-degradable polymers such as polyacrylamide or polyacrylate. The non-degradable constituent of the block copolymer may cause complications in clinical applications. Therefore, reduction-responsive core-crosslinked micelles comprising entirely of biologically inert or biocompatible and biodegradable polymers would be better candidates for drug delivery and controlled release application. To overcome these limitations, micelles based on polyesters (a class of aliphatic biodegradable polymers) can used for drug delivery application. In the last few decades, various FDA approved aliphatic polyesters e.g. poly(lactic-co-glycolic acid) (PLGA), poly(ε-caprolactone), and poly(lactic acid), have been intensively studied to exploit their potential in drug, gene and protein delivery and controlled release applications. Nevertheless, most of these polyesters lack functional groups, making it difficult to incorporate redox-responsive linkages to core-crosslink their micelles. To address these issues, we have synthesised functional biodegradable and biocompatible block copolymers based on methoxypoly(ethyleneglycol)-b-poly(-caprolactone-co--azido--caprolactone) (mPEG-b-poly(CL-co-N3CL)). The pendent chloro groups of the block copolymer were converted into azides using nucleophilic substitution reaction to obtain mPEG-b-poly(CL-co-N3CL) block copolymer as a precursor of reactive polymeric micelles. The synthesised polymers were characterised by NMR, FT-IR and size exclusion chromatography (SEC). Micelles were prepared using the dialysis method and methotrexate (an anticancer drug) was loaded into the hydrophobic core of the reactive micelles. Micelles were subsequently crosslinked by a redox-responsive bis-alkyne ethyl disulfide crosslinker. The size distributions and morphology of core-crosslinked micelles were assessed using dynamic light scattering (DLS) and transmission electron microscopy. The drug release studies were performed under simulated non-reducing and reducing conditions. Cellular uptake studies in human breast cancer cells (MCF7 cells) were performed using Oregon-green loaded core-crosslinked micelles. The MTX-loaded core-crosslinked micelles were assessed for their cytotoxicity in human breast cancer cells by MTT assays. The apoptosis inducing potential of MTX-loaded core-crosslinked micelles was analysed using Hoechst/PI assays and was further probed by annexin-V/PI assays. The data from these studies indicate that drug release from these crosslinked micelles can be controlled and that redox-responsive micelles are more effective carriers for MTX than non-cross-linked analogues in the cell lines tested. In another strategy, a multifunctional amphiphilic block copolymer based on -amine-PEG-b-poly(CL-co-N3CL) was synthesised and subsequently was used to conjugate methotrexate on the hydrophilic block for receptor mediated targeting of breast cancer cells. Cellular uptake studies revealed 2.3-fold higher uptake of MTX-conjugated micelles as compared with un-conjugated micelles. The blank micelles showed low cytotoxicities in breast cancer cells, however, MTX-conjugated micelles exhibited greater antitumor activity in contrast to the free-MTX. We hypothesise that these functional micelles could be potentially powerful nanocarriers for stimuli-responsive controlled release, active tumour targeting, and cancer therapy.